A comparison of unawareness in frontotemporal dementia and Alzheimer's disease. Issue 2 (26th September 2007) - Salmon, E; Perani, D; Collette, F; Feyers, D; Kalbe, E; Holthoff, V; Sorbi, S; Herholz, K
Abstract : Background: Loss of insight is a core diagnostic feature of frontotemporal dementia (FTD) and anosognosia is frequently reported in Alzheimer's disease (AD). Aim: To compare unawareness (anosognosia) for different symptoms, measured with a discrepancy score between patient's and caregiver's assessment, in AD and FTD. Method: In a prospective, multi-centre study, 123 patients with probable AD, selected according to the NINCDS-ADRDA procedure, were matched for age, sex, education, disease duration and dementia severity to patients with FTD (n = 41), selected according to international consensus criteria. A research complaint questionnaire was used to obtained patient's and caregiver's assessment concerning neuropsychological and behavioural symptoms. Data were compared in each group and between groups. Unawareness (measured by discrepancy scores) was compared between patients with AD and FTD. Results: The caregivers generally assessed symptoms more severely than did patients, but both patient groups reported changes in affect (depressive mood or irritability) as their caregivers did. Unawareness was greater in patients with FTD than in patients with AD for language and executive difficulties, and for changes in behaviour and daily activities. Conclusion: The main finding is that unawareness was observed in both patients with FTD and patients with AD for most clinical domains. However, qualitative and quantitative differences showed that lack of awareness was greater in patients with FTD.